The research of antibacterial properties of decamethoxin, decasan, horosten - H. K. Palii; A. O. Dudar; S. V. Pavliuk; O. A. Nazarchuk; D. V. Palii; A. V. Kulyk (Kazimierz Wielki University, 2019)
The study of Staphylococcus resistance to the antibacterial drugs Decamethoxin, Decasan, Horosten remains an important medical problem. The aim of this study was to investigate the antistaphylococcal properties of Decamethoxin, Decasan, Horosten. It has been proven that qaterinary ammonium antiseptic drugs (Decamethoxin, Decasan, Horosten) have high antistaphylococcal properties. The bactericidal activity of Decamethoxin has been shown to be stable under adverse pH conditions of different microbial loading. Different concentrations of Decamethoxine have been shown to cause the formation of resistant variants of Staphylococcus, which lose the ability to form pigments and enzymes.